IAB-BAMF-SOEP Survey of Refugees - 2023: Sampling, nonresponse, and weighting of the sample M9 - Hans Walter Steinhauer; Manuel Siegert; Felix Süttmann; Rainer Siegers; Sabine Zinn (Deutsches Institut für Wirtschaftsforschung (DIW), German Socio-Economic Panel (SOEP), 2025)
This paper outlines the sampling and weighting process for the M9 sample, an augmentation sample for the IAB-BAMF-SOEP Survey of Refugees. It augments the samples M3, M4, M5, and M6 with refugees entering Germany between January 1, 2017, and the August 31, 2022. It also adds refugees from Ukraine by including those who entered Germany in the period from June 9, 2022 up to and including August 31, 2022. The sample is drawn from the Central Register of Foreigners (Ausländerzentralregister; AZR) in a stratified two-stage design. At the first stage clusters of districts are sampled and at the second stage refugees are sampled as anchor persons for the household. Design weights are adjusted to correct for nonresponse and coverage. Nonresponse adjustments make use of design information, interviewer characteristics, arealevel and regional information, as well as information from the AZR. The marginal distributions we use for post-stratification are derived from the AZR as well. The M9 sample and its weights are seamlessly integrated into the IAB-BAMF-SOEP Survey of Refugees and the SOEP.
Keywords: 330